The dynamics of foreign direct investment and exchange rates: An interconnection approach in ASEAN - Ferry Syarifuddin (Cogent Economics & Finance, 2022)
This paper examines the direct and spillover effects of exchange rate on foreign direct investment (FDI) inflows in a panel of ASEAN countries from 2001 to 2018. We utilize the spatial econometric approach to accommodate the nature of spatial dependence among ASEAN countries. Our results suggest that the effect of the exchange rate depends on the source-region of FDI, implying the existence of spatial heterogeneity in ASEAN's FDI. We also show that FDI inflows in ASEAN are not only influenced by the exchange rate of the country itself but also by those of the neighboring countries.
Keywords: 330; Foreign direct investment; exchange rates; macroeconomics; spatial models